Assessing Mathematics Classroom Goal Structures in a Sample of Italian Students During Sixth Grade. (March 2018) - Poliandri, Donatella; Sette, Stefania; Vinci, Emanuela; Romiti, Sara
The present study analyzed the factor validity of the Patterns of Adaptive Learning Scale (PALS) to assess students' perceptions of mathematics classroom goal structures. Participants were N = 7, 773 Italian students aged from 11 to 15 years ( M = 11.97, SD = 0.50). The confirmatory factor analysis replicated a three-factor structure (i.e., mastery, performance-avoidance, and performance-approach goals) of the scale. Multigroup confirmatory factor analyses supported configural, metric, and scalar measurement invariance of the scale across gender. Moreover, the students' mathematics achievement was positively related to mastery goals and negatively associated with performance-avoidance goals. The use of the scale may help teachers to understand the relations between classroom goal structures and mathematics achievement during middle school.